2013
DOI: 10.1038/ni.2756
|View full text |Cite
|
Sign up to set email alerts
|

ELF4 is critical for induction of type I interferon and the host antiviral response

Abstract: Induction of type I interferon is a central event of innate immunity, essential for host defense. Here we report that the transcription factor ELF4 is induced by type I interferon and upregulates interferon expression in a feed-forward loop. ELF4 deficiency leads to reduced interferon production, resulting in enhanced susceptibility to West Nile virus encephalitis in mice. After viral infection, ELF4 is recruited by STING, interacts with and is activated by the MAVS-TBK1 complex, and translocates into the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 48 publications
6
130
3
Order By: Relevance
“…ULK1 and ELF4 were recently implicated in the regulation of STING-dependent signaling (39,49). As AMPK has been shown to interact with ULK1 (50), we hypothesized that, in the absence of AMPK, ULK1 would repress STING-dependent signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ULK1 and ELF4 were recently implicated in the regulation of STING-dependent signaling (39,49). As AMPK has been shown to interact with ULK1 (50), we hypothesized that, in the absence of AMPK, ULK1 would repress STING-dependent signaling.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that this was caused by an increase in viral replication, VSV-G protein was monitored by Western blot analysis. By 6 h post-infection, VSV-G protein A Previously Identified Regulator of STING Signaling, ULK1, Is Constitutively Dephosphorylated in AMPK-deficient Cells-ULK1 and ELF4 have been demonstrated recently to regulate STING-dependent signaling in opposing fashions: ELF4 enhances STING-dependent signaling by binding to regulatory sites within the IFN-␤ promoter, thereby increasing the binding affinity of IRF3 and IRF7 to interferon-sensitive response elements within the IFN-␤ promoter (49). Conversely, the ULK1 kinase has been reported to inhibit STING-dependent IRF3 phosphorylation by phosphorylating the Ser-366 residue of STING to prevent recruitment of IRF3 (39).…”
Section: Ampk-deficient Mefs Exhibit Impaired Vsv-dependent Ifn-␤ Expmentioning
confidence: 99%
“…The transcription factors ELF4 and IRF5 both have been implicated as participants in the MAVS-dependent induction of IFN-␤ after WNV infection. A deficiency of ELF4 resulted in reduced type I IFN production after WNV infection in mice (13). ELF4 translocates into the nucleus after MAVS-dependent activation, binds to IFN promoters, and cooperatively increases the binding affinity of IRF3 and IRF7 (13).…”
mentioning
confidence: 99%
“…The group also demonstrated that ELF4 acts as an IFN transcription factor, as it has the potential to increase the binding affinity of IRF3 and IRF7 through cooperative binding to newly identified enhancer elements (EICE) in the IFN promoters. 1 These new findings not only extend our knowledge about the details of the fine-tuning of the innate IFN responses, but also represent a new milestone by describing the role of EICE elements in this process.…”
mentioning
confidence: 55%